Coastal Atmosphere and Sea Time Series (CoASTS) and Bio-Optical mapping of Marine Properties (BiOMaP): the CoASTS-BiOMaP dataset - G. Zibordi; G. Zibordi; J.-F. Berthon (Earth System Science Data)
The Coastal Atmosphere and Sea Time Series (CoASTS) and Bio-Optical mapping of Marine Properties (BiOMaP) programs produced bio-optical data supporting satellite ocean color applications for more than 2 decades. Specifically, relying on the Acqua Alta Oceanographic Tower (AAOT) in the northern Adriatic Sea, from 1995 till 2016 CoASTS produced time series of marine water apparent and inherent optical properties, in addition to the concentration of major optically significant water constituents. Almost concurrently, from 2000 till 2022 BiOMaP produced equivalent spatially distributed measurements across major European seas. Both CoASTS and BiOMaP applied standardized instruments, measurement methods, quality control schemes and processing codes to ensure temporal and spatial consistency in data products. This work presents the CoASTS and BiOMaP near-surface data product, named CoASTS-BiOMaP, which is of relevance to ocean color bio-optical modeling and validation activities. The data are available at https://doi.org/10.1594/PANGAEA.971945 (Zibordi and Berthon, 2024).